A technical analysis of market efficiency of emerging economies: the case of BRICS countries - Kretzschmar, Joshua Heath (The IIE, 2024)
The concept, also known as the efficient market hypothesis (EMH), is a subject of debate in the field of finance. Proponents of the EMH theory claim that it offers a foundation for understanding financial markets, but opponents claim that the theory is irrational in its assumptions about the actual functioning of these markets. While the EMH may be flawed, it offers an acceptable foundation for analysing financial markets. In recent years, researchers have broadly analysed the efficiency of markets, mainly in developed and well-established financial markets. However, there has been a scarcity of studies conducted on emerging economies. Hence, this study investigates the weak-form EMH of the BRICS to determine whether the financial markets of Brazil, Russia, India, China, and South Africa may be considered weak-form efficient. This study analysed the BRICS and four benchmark economies using daily observations from 16th January 1995 to 16th June 2023, divided into six periods to identify if specific economic events impacted the market efficiency. Analysis was carried out using various statistical tests, i.e., ARMA, GARCH, Variance ratio, Runs test, Cox-Stuart test, Bartels test, Difference Sign test and Mann-Kendall test. Ultimately, the findings were that BRICS countries' markets are efficient markets and follow a weak-form efficiency, and specific patterns or trends could be identified in some cases that could be profitable for investors. This study recommends valuable insight for investors and policymakers of how they can use a hedge strategy to hold more assets in emerging economies that are weak-from EMH.
Keywords: Efficient market hypothesis; Financial markets; BRICS; Economies